Informação e participação social no turismo sustentável: o caso da zona portuária da cidade do Rio de Janeiro. - Bittencourt, Yolle Vacariuc (2014)
This work is an analysis of the information on the dynamics of Social Participation regarding the implementation of touristic activity. Tourism is an economic activity in great expansion, and has presented itself as an important strategy in urban politics to leverage local economy and promote cities in international markets. Urban requalification of old cities centers and portuary installations is a global tendency in urban policies, which aims to orient cities towards a new centrality, by means of increasing housing market value, and empowering tertiary sector economical activities, specially tourism. The main objective of this work is to investigate the informational dynamics of the main social actors involved in the implementation process of Porto Maravilha project in the portuary installation area of Rio de Janeiro. The methodology of work is based on bibliographical analysis, internet and social media material and interviews with employees or representatives of the government and private initiatives, and the local populace of Morro da Providência, a community selected for its major historical and cultural value. To set the context of the theoretical framework, we discuss the intrinsical relation between sustainable tourism, information and social participation, considering that the touristification of any region should be a democratic and socially inclusive process, being the participation of local population a fundamental part, from the planning stages of the project until its very implementation, governance and the socialization of its benefits. We've adopted the concept of tourism advised by Wersig, in which information is considered the knowledge necessary to act. From this theoretical framework it has been possible to establish the link between the concepts that are the basis for this work and to analyze the case regarding the portuary installation in Rio de Janeiro, specially the Morro da Providência community, main stage for several conflicts due to remotion of local population from their homes. The analysis of informational production from the social actors (community inhabitants, official institutions and government associates) demonstrates the contrast between different speeches in a territory stained by struggle and social conflicts. On the other hand, the local populace, with the aid of social media, was able to organize their own mobilization and resistance, by means of broadcasting their own points of view.